Direct aspiration stroke thrombectomy: a comprehensive review. (12th June 2020) - Boisseau, William; Escalard, Simon; Fahed, Robert; Lapergue, Bertrand; Smajda, Stanislas; Maier, Benjamin; Desilles, Jean Philippe; Delvoye, François; Ciccio, Gabriele; Redjem, Hocine; Hebert, Solène; Ben Maacha, Malek; et al.
Abstract : Mechanical thrombectomy is now the standard of care for acute ischemic stroke patients with large vessel occlusions, and can be performed with several devices and techniques. One of these techniques, direct aspiration (DA), consists of navigating a large-bore catheter up to the face of the clot and initiating forceful suction. This comprehensive review has three objectives: (1) to describe the direct aspiration technique; (2) to present the available evidence regarding predictive factors of DA success and performance compared with other techniques; and (3) to discuss the forthcoming improvements in distal aspiration.